PENGARUH LEADERSHIP, SOFT SKILL, DAN PRESTASI BELAJAR TERHADAP KEIKUTSERTAAN MAHASISWA DALAM BERORGANISASI DI FAKULTAS EKONOMI DAN BISNIS UNP KEDIRI - Ika, Putri Kirana Oktaviani; Prastyaningtyas, Efa Wahyu; Lukiani, Eunike Rose Mita (Universitas Nusantara PGRI Kediri, 2024)
This study aims to examine the extent to which leadership, soft skills, and academic performance affect student engagement in organizations. This investigation employs a quantitative methodology, utilizing a questionnaire for data collection. The study's population comprises students from the Faculty of Economics and Business at UNP Kediri, specifically those involved in organizations, totaling 172 participants. A purposive sampling technique was applied, resulting in a sample size of 63 students. Data analysis was conducted using SPSS version 24, revealing a t-test value for the leadership variable with a significance level of 0.00, which is less than 0.05, indicating a significant impact. Similarly, the t-test for the soft skills variable yielded a significance level of 0.02, also below 0.05, demonstrating a notable effect. The analysis of the learning achievement variable, represented by a commendable GPA of 4.00, further supports these findings. The results of the F-test indicated that the significance value exceeded the critical F-table value of 335.080, confirming that leadership, soft skills, and academic performance collectively influence student participation in organizations within the Faculty of Economics and Business at UNP Kediri.